Is inspiratory muscle strength related with functional capacity? - Francisco, R. (2017)
Introduction: The decrease in inspiratory muscle strength may affect the respiratory health, especially in the elderly. Generally, the handgrip strength is used as a functional capacity indicator. Thus, our objective was to verify inspiratory muscle strength in a sample of elderly and investigate possible associations with measured handgrip strength. Methods: Maximal inspiratory pressure (MIP in cmH2O)was assessed using a dynamometer for respiratory muscles (MicroRPM®), whereas handgrip strength (HG in kg) was evaluated using a hydraulic dynamometer (JAMAR®). Body mass index (BMI in kg/m2) was calculated from weight (kg) and height (m). The association between MIP and HG was analyzed based on Spearman’s rank correlation coefficient for p < 0.05. Results: A sample of 21 older day-care center attendants (2 males and 19 females) aged 79 ± 6 years old with a BMI (29.6 ± 3.5 kg/m2) were assessed. MIP scored 64.0 ± 19.8 cmH2O for males (around 65% of the expected 98.2 ± 2.7 cmH2O) and 39.1 ± 19.5 cmH2O for females (around 60% of the expected 64.1 ± 3.2 cmH2O). Moreover, an HG of around 30.0 ± 9.9 kg and 24.2 ± 3.9 kg was obtained for males and females, respectively, which were below average for both genders. Lastly, a positive relation indicator between HG and MIP was attained with p = 0.001 and rs = 0.660. Conclusions: Results suggest an association between the diminishing of MIP and the decreasing of the functional capacity measured by the HG, indicating the importance of inspiratory muscle training in elderly. Nevertheless, further studies with larger samples are recommended to validate these results.